2022
DOI: 10.1002/slct.202103804
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Isomerization of Glucose to Fructose Catalyzed by Guanidinium Ionic Liquids

Abstract: The isomerization of glucose to fructose is the rate determining step in many techniques for chemo‐catalytic conversion of cellulosic biomass to highly value‐added biochemicals. However, current techniques are generally challenging by poor process efficiency, low fructose yield and selectivity, etc. Therefore, the exploitations of novel catalytic systems for the efficient isomerization of glucose are important and highly desired. Herein, a series of biodegradable guanidinium ionic liquids were synthesized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The induction time was observed for a number of soluble catalysts including KOH, 19 NaOH, 22 phosphate buffer, 64 amines, 45,91 and guanidinium ionic liquids. 92 At conversions of 20−30%, a maximum selectivity for Fru is attained; at higher conversions, selectivity decreases due to decomposition. The selectivity− conversion curves present thus volcano-shaped plots.…”
Section: Catalysis By Soluble Basesmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction time was observed for a number of soluble catalysts including KOH, 19 NaOH, 22 phosphate buffer, 64 amines, 45,91 and guanidinium ionic liquids. 92 At conversions of 20−30%, a maximum selectivity for Fru is attained; at higher conversions, selectivity decreases due to decomposition. The selectivity− conversion curves present thus volcano-shaped plots.…”
Section: Catalysis By Soluble Basesmentioning
confidence: 99%
“…Under the reaction conditions, enediolates are prone to degradation processes, leading to low selectivity, as described in Section . The induction time was observed for a number of soluble catalysts including KOH, NaOH, phosphate buffer, amines, , and guanidinium ionic liquids . At conversions of 20–30%, a maximum selectivity for Fru is attained; at higher conversions, selectivity decreases due to decomposition.…”
Section: Catalysis By Soluble Basesmentioning
confidence: 99%
“…Long et al have investigated the application of guanidium-based ILs in the successful chemo-catalytic isomerization of glucose (66) into fructose (67) (Scheme 19). 76 A total of fourteen guanidinium based ILs were synthesized and screened for the conversion of 66 into 67. It was found that the basic strength of the ionic liquid, along with its catalytic amount, reaction temperature, reaction time, and solvent played key roles in the formation of 67, where the highest yield (34%) was obtained upon the treatment of 66 with tetramethyl guanidinium proline [TMG][Pro] at 80 °C for 30 minutes in H 2 O.…”
Section: Guanidinium-based Ionic Liquidsmentioning
confidence: 99%
“…It has been noticed that basic ILs composed of [N 4,4,4,4 ]Pro (tetrabutyl ammonium proline) and [TMG]Pro (tetramethyl guanidinium proline) have the tendency to efficiently isomerize glucose into fructose. 18,19 Likewise, the catalytic conversion of n -hexane to the corresponding branching isomers with a low conversion yield of 11.52% to 36.30% has been observed with three distinct imidazolium and pyridinium-based chloroaluminate ILs. 20 IL-supported metal complexes for the isomerization reactions can be seen in various reports.…”
Section: Introductionmentioning
confidence: 98%